NKG2D Ligands–Critical Targets for Cancer Immune Escape and Therapy - Schmiedel, Dominik; Mandelboim, Ofer (Frontiers in Immunology, 2018)
DNA damage, oncogene activation and excessive proliferation, chromatin modulations or oxidative stress are all important hallmarks of cancer. Interestingly, all of these abnormalities also induce a cellular stress response. By upregulating “stress-induced ligands”, damaged or transformed cells can be recognized by immune cells and cleared. The human genome encodes eight functional “stress-induced ligands”: MICA, MICB and ULBP1-6. All of them are recognized by a single receptor, NKG2D, which is expressed on natural killer (NK) cells, cytotoxic T cells and other T cell subsets. The NKG2D ligand/NKG2D-axis is well-recognized as an important mediator of anti-tumor activity; however, patient data about the role of NKG2D ligands in immune surveillance and escape appears conflicting. As these ligands are often actively transcribed, tumor cells are urged to manipulate the expression of these ligands on post-transcriptional or post-translational level. Although our knowledge on the regulation of NKG2D ligand expression remains fragmentary, research of the past years revealed multiple cellular mechanisms that are adopted by tumor cells to reduce the expression of “stress-induced ligands” and therefore escape immune recognition. Here, we review the post-transcriptional and post-translational mechanisms by which NKG2D ligands are modulated in cancer cells and their impact on patient prognosis. We discuss controversies and approaches to apply our understanding of the NKG2D ligand/NKG2D-axis for cancer therapy.